An Investigation of People with Persistent Low Back Pain and High Pain-Related Fear - Torres Caneiro, Joao Paulo (Curtin University, 2018)
Pain that is interpreted as threatening can lead to fear, avoidance and disengagement from valued activities. Low back pain (LBP) associated with high pain-related fear is disabling. The body of work presented in this doctoral thesis aims to better understand the relationship between pain, fear and disability; and how the process of change unfolds for individuals with persistent LBP and high pain-related fear over the course of an exposure-based behavioural intervention.